TINGKAT KESEJAHTERAAN PETANI SALAK DI DESA TINJOMAN LAMA KECAMATAN PADANGSIDIMPUAN HUTAIMBARU KOTA PADANGSIDEMPUAN - KHOIRUNNISA PASARIBU; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Tinjoman Lama District of Padangsidimpuan Hutaimbaru Padangsidimpuan City with three research question (1) How are the welfare of farmers in the village barking Tinjoman Lama? (2) What are the constraints faced by farmers bark in improving welfare of society in the Tinjoman village? (3) How are the government's role in improving welfare of farmers in the village barking Tinjoman Lama? The purpose of this study to determine level of welfare of farmers bark, knowing the constraints faced by the community and government's role in improving the welfare of farmers in the village barking Tinjomam Lama District of Padangsidimpuan Hutaimbaru Padangsdimpuan City. This study is a descriptive quantitative research. The population in this study were all barking farmers in the village of Tinjoman Lama. The sample of this study a total of 36 respondents (50%) of the overall polpulations using random sampling technique, that is by knowing all the farmers barking then randomized based on the name for the next interview. To collect the data the researchers use methods of literary study (study library), observation (observation) and interview (interview) by using the interview guide as a reference to obtain information in analyzing the research data used quantitative analysis and descriptive described. Based on the study concluded that the level of welfare of all farmers bark is at the level of the Family Welfare I that families who have been able to meet basic needs (basic needs) is minimal and is able to meet the needs of social psychology (Social psychological needs). Constraints faced by farmers bark which has a land area that is relatively low, so the marketing media minimal impact on farmers' income is low. Lack of government's role in improving the welfare of farmers bark that can be seen from the absence of assistance in the form of marketing, production quality improvement, education / training in agriculture, provision of quality seeds and fertilizers or appropriate technology.Keywords: Farmers, bark, welfare, role of government.